PENENTUAN STRATEGI PEMASARAN DAN USULAN PERANCANGAN ULANG KEMASAN PRODUK PADA UMKM KOTA GEDE - Shinta Devi, Fitria; Rochim, Alfin Arif; Santoso, Risdya; Jati Nugroho, Andung (CV. ALIM'SPUBLISHING, 2023)
Every business must strive to remain stable in its performance in order to survive competition. In Kotagede Yogyakarta, UMKM Yangko Sari Roso produces food. Businesses that are developing in the current era of globalization are characterized by strong competition in all fields, such as business in industry, trade and services. Because the company only produces for one shop and entrusts products to several distributors, Yangko's MSME sales strategy is still not well chosen. In addition, making product packaging that is considered quite expensive and unattractive results in poor sales, which results in high inventories in warehouses and cost losses. The ultimate goal of this work is to find the best solution to the problem of marketing and production costs. The ARIMA method is used to forecast Yangko's short-term sales, production costs, and packaging proposals. The aim of this method is to provide the best results for finding marketing decisions. The results of this research, namely the analysis of marketing strategy observations, show that the company can overcome this problem and find ways to make production costs more efficient by increasing labor.